Urgensi Kualitas Pelayanan Bagi Penumpang Transportasi - Rachmat; Nanang Juhandi (Asosiasi Ahli Administrasi Indonesia, 2020)
This research analyzes the effect of service quality on passengers' satisfaction. The method used in this research is the sampling incidental method. The total sample of this research is 150 people. Quantitative data analysis methods are used to discuss the problems. The object of this research is a transportation company. This research will discuss the effect of service quality on satisfaction received by the passengers. It should be said that the company has provided a fairly good service quality to passengers so that they feel quite satisfied with the quality provided. However, the company will continue to strive to be better in improving service quality so that passengers' satisfaction is met properly.